What’s in a Perspective? - Ege Yumuşak (Feminist Philosophy Quarterly)
Philosophers of mind and epistemology have studied extensively what beliefs are and what we ought to believe. Yet we are guided toward many of our beliefs by our perspectives: cognitive structures that guide how we see and think. A chief role of ordinary perspective talk is to describe clashes between different points of view that arise when people interact. In this paper, I argue that the most developed extant account of perspectives, Elisabeth Camp’s, lacks the resources to analyze interactions between perspectives. By contrast, my account of perspectives—the agenda view—better captures the kinds of differences and confrontations that underlie ordinary perspective talk by focusing on the “zetetic” role of perspectives in directing inquiry.